Food and nutritional surveillance: Coverage and characterization for children under 2 years of Northeast Brazil (Research, Society and Development, 2021)
Objective: To evaluate the coverage of the Food and Nutritional Surveillance System (SISVAN) for children under 2 years of age in Northeastern Brazil and to characterize their nutritional status and food consumption, according to sex and data source, in 2019. Methodology: This is a cross-sectional study, whose data collection was carried out through public reports of SISVAN. Association analyzes were performed using the chi-square test, considering values of p